Design and elaboration of a tractable tricyclic scaffold to synthesize druglike inhibitors of dipeptidyl peptidase-4 (DPP-4), antagonists of the C–C Chemokine Receptor Type 5 (CCR5), and highly potent and selective phosphoinositol-3 Kinase δ (PI3Kδ) inhibitors - Schwehm, Carolin; Kellam, Barrie; Garces, Aimie; Hill, Stephen J.; Kindon, Nicholas; Bradshaw, Tracey D.; Li, Jin; Macdonald, Simon J.F.; Rowedder, James E.; Stoddart, Leigh A.; Stocks, Michael (American Chemical Society, 2017)
A novel molecular scaffold has been synthesized, and its incorporation into new analogues of biologically active molecules across multiple target classes will be discussed. In these studies, we have shown use of the tricyclic scaffold to synthesize potent inhibitors of the serine peptidase DPP-4, antagonists of the CCR5 receptor, and highly potent and selective PI3K δ isoform inhibitors. We also describe the predicted physicochemical properties of the resulting inhibitors and conclude that the tractable molecular scaffold could have potential application in future drug discovery programs.